Investigating Consumer Purchasing Decisions Of Convenience Products Nowadays: The Effect Of Customer’s Character, Pricing, And Digital Marketing - Murti, Lita Indira; Maharani, Anita; Pujiwati, Ami (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2024)
The aim of this study was to explore consumer purchasing decisions of convenience products specifically daily use cosmetic. This study elaborates several concepts related to factors of consumer purchasing decisions. However, this study follows quantitative approach, this research collects data through survey distribution to all daily use cosmetic and was collected 96 respondents and to analysis the data, researcher undergo through several techniques, that were ANOVA, and t-test. Based on the results of the study, factors affecting consumer’s purchasing decisions was significantly influenced by consumer character, pricing, digital marketing.